Use of non-invasive ventilation to facilitate extubation in a patient with amyotrophic lateral sclerosis with hypercapnic respiratory failure - Montserrat Diaz-Abad; Chandana Chauhan; Denise Epps; James W. Russell; Justin Kwan (MDPI AG, 2019)
We present the case of a 44-year-old man with amyotrophic lateral sclerosis (ALS) intubated for hypercapnic respiratory failure and aspiration pneumonia. The patient was successfully extubated, transitioned to non-invasive ventilation and lived at home comfortably for 17 months, with good functional status for the first year. This case highlights the potential of prolonged survival post extubation in patients with advanced ALS and respiratory failure. The patient was managed post-discharge in a multidisciplinary ALS clinic by experienced neuromuscular and pulmonary specialists.